2022
DOI: 10.3390/ijms23147885
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genomic Analysis of a New Phage Infecting Helicobacter pylori

Abstract: Helicobacter pylori, a significant human gastric pathogen, has been demonstrating increased antibiotic resistance, causing difficulties in infection treatment. It is therefore important to develop alternatives or complementary approaches to antibiotics to tackle H. pylori infections, and (bacterio)phages have proven to be effective antibacterial agents. In this work, prophage isolation was attempted using H. pylori strains and UV radiation. One phage was isolated and further characterized to assess potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…As the mechanism of phage bactericidal activity is completely different from that of antibacterial drugs, phage therapy is expected to be an attractive approach to addressing the multidrug resistance of H. pylori . However several human gut microbiota research studies have demonstrated that phages perform a function in intestinal homeostasis ( Ferreira et al, 2022 ). Currently, phages are thought to precisely affect the intestinal microbiota and exert beneficial effects on numerous gastrointestinal disorders ( Muñoz et al, 2020 ).…”
Section: Main Textmentioning
confidence: 99%
“…As the mechanism of phage bactericidal activity is completely different from that of antibacterial drugs, phage therapy is expected to be an attractive approach to addressing the multidrug resistance of H. pylori . However several human gut microbiota research studies have demonstrated that phages perform a function in intestinal homeostasis ( Ferreira et al, 2022 ). Currently, phages are thought to precisely affect the intestinal microbiota and exert beneficial effects on numerous gastrointestinal disorders ( Muñoz et al, 2020 ).…”
Section: Main Textmentioning
confidence: 99%
“…As indicated, other prophages have been identified in Hp. Some of them (HP1, KHP30, PhiHp33, HPy1R...), after excitation can infect and induce Hp lysis, even under conditions similar to those of the gastric environment [21,41]. The question remains whether Malian prophages (HpMLpΦ) are genetically diverse on all genes and if after excision of the bacterial genome the virions produced have lytic activity on the HpML strains in the extreme conditions of the stomach.…”
Section: Hpml Diversity (Caga and Int)mentioning
confidence: 99%